E6/E7 oncoproteins of high risk HPV-16 upregulate MT1-MMP, MMP-2 and MMP-9 and promote the migration of cervical cancer cells - Zhu, Dingjun (Int J Clin Exp Pathol, 2015)
Background: E6 and E7 of high risk human papillomavirus 16 (HPV16) were reported to correlate with the cervical cancer (CC). And the presence of matrix metalloproteinases (MMPs) has also been indicated to be associated with CC. Methods: The present study investigated the expression of MMPs (MT1-MMP, MMP-2 and MMP-9) in CC cells with HPV16-E6/E7 oncoprotein(s) negative or positive, and then determined the regulation of HPV16-E6/E7 oncoproteins on the expression of MMPs (MT1-MMP, MMP-2 and MMP-9) and the migration of cervical cancer Caski and SiHa cells with RNAi technology. Results: It was demonstrated that the overexpression or the knockdown of HPV16-E6/E7 promoted or reduced MT1-MMP, MMP-2 and MMP-9 in CC cells. And the HPV16-E6, -E7 or -E6E7 influenced the migration of CC cells. The overexpression or the knockdown of them promoted or inhibited the migration of C33A or Caski/SiHa cells. Moreover, the chemical inhibition of MMP-2 or MMP-9 significantly reduced the migration of CC Caski or SiHa cells. Conclusions: Our results demonstrated that the E6-HPV16 or E7-HPV16 promoted the activity of MMP-2/9, and contributed to the migration of cervical cells.